Differential Yield, Nutrient Uptake and Water Productivity of Rice Cultivars under Aerobic Conditions on Alfisols of a Semi-arid Environment - Ramanjaneyulu, A. V.; Madhavi, A.; Neelima, T. L.; Basha, S. Ameer; Singh, T. V. K.; Reddy, D. Madhusudhan; Shashibhushan, D.; Shankar, V. Gouri; Jagadeeshwar, R. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted for three years (kharif seasons of 2007, 2008 and 2009) RARS (PJTSAU), Palem, Telangana state, India to study the yield and nutrient uptake of ten diverse popular high yielding low land rice varieties under aerobic conditions in relation to weather. The pooled analysis revealed that JGL-11727, MTU-1001 followed by MTU-1010 have performed better than other varieties with respect to yield attributes, yield and water productivity. JGL-11727 variety of rice has consumed significantly greater amounts of N and K than other varieties, barring MTU-1001 and MTU 1010. Regarding P mining by grain, straw and total plant, JGL-11727 was found to be more efficient. Of all varieties used in experimentation, Tellahamsa removed significantly less amount of N, P and K besides recording less protein content owing to its shorter duration. JGL-11727 variety has recorded higher mean water productivity (0.28 kg m-3) and was the only variety with positive net returns (` 3012 ha-1).